Correlation of Lymphocyte-Monocyte Ratio with Grading of Breast Cancer Malignancy - Suharyani; Muhartono Muhartono; Rizki Hanriko (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2020)
Introduction: Breast cancer cases are increase and fast becoming the leading cause of oncologic mortality among women worldwide. Delay in management will worsen the prognosis of breast cancer patients. The poor prognosis is correlate with high grade of breast cancer malignancy. Histology can be used as an indicator to assess the grade of breast cancer malignancy. In addition, a high predictive value of lymphocyte-monocyte ratio (LMR) has been suggested to indicate favorable prognosis of various cancer, and used as parameters for assessing breast cancer prognosis. Method: This study is a quantitative research, using an observational approach. Laboratory examination results are collected from 43 breast cancer patients who will conduct treatment at Urip Sumoharjo Hospital from June to September 2019. Data are processed by the Spearman rank test using SPSS 22.0. Results: Correlation test results between lymphocyte-monocyte ratio with histological grading of breast cancer obtained a P value of 0.376. Conclusions: Lymphocytes to monocytes ratio (LMR) value cannot be utilize as a parameter for evaluating prognosis of breast cancer.